Soil physical behaviour and rice (Oryza sativa) yield under different sources of organics, methods of puddling and zero tillage - Mishra, V K; Saha, R (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during 2000-04 in foothill sandy clay loam soil (Typic Hapludalf) of Meghalaya. The treatments included 4 tillage practices (no tillage, puddling with spade, power tiller cultivator mounted with cage wheel and desi plough) and 4 sources of organics (no organic, forest grass, Ambrosia sp. and farmyard manure). After 5 years, puddling with power tiller increased the bulk density (19.4%), penetration resistance (24.0%), and decreased organic carbon (9.4 %), mean weight diameter (26.4%) and hydraulic conductivity (14.6%) over the initial value of soil. Reverse trends for corresponding parameters were recorded under zero tillage. The storage pores ranged between 36.7 and 41.4 % for puddle plots compared with the 52.6 % for the zero tillage plots. The percolation rate of water was also affected by the tillage. At 24 hr of 6 cm water application, the water reached up to 90 and 75 cm depth with retention of 84.0 and 96.3 % of the total applied water under puddling with power tiller and zero tillage, respectively. The earthworm casting as indicator of earthworm activities increased by 58.5% under the zero tillage over the puddled condition. Initially, for 3 years the rice grain yield was lower under zero tillage. However, after 3 years the yield was higher (3.43 to 3.66 tonnes /ha ) under zero tillage than that of puddle plots (3.06 to3.58 tonnes/ha). Among the different source of organics, farmyard manure was the best for production of rice grain yield. Ambrosia sp. was also found a promising weed as a green manure crop.